Quality of Life, Self-Esteem, and Stress among First-Semester Student Nurses in Indonesia: A Cross-Sectional Study - Maria Komariah BSN, RN, MHSc, PhD; Theresia Eriyani BSN, RN, MHL; Laili Rahayuwati BSc, MS, PhD; Hana Rizmadewi Agustina BSN, RN, MN, PhD; Furkon Nurhakim BSN, RN, MM; Irman Somantri BSN, RN, MNM; Shurouq Ghalib Qadous BSN, RN, MNS, PhD; Aurawan Janmanee BSN, RN, MNS, PhD; Nina Gartika BSN, RN, MNS (SAGE Open Nursing)
Introduction College presents students with various new challenges, including changes in environment, learning methods, friendships, and other unfamiliar situations, potentially triggering mental health issues. Recent epidemiological data show that the prevalence of depression and stress among college students aged 18–24 years is 37.2% and 23.7%, respectively. Objective This study aimed to determine the circumstances and factors affecting the quality of life, self-esteem, and stress of first-year undergraduate nursing students in Indonesia. Methods In total, 300 nursing students were recruited to participate in a quantitative descriptive cross-sectional mental health survey to determine the quality of life, self-esteem, and stress levels of first-semester students across multiple nursing education centers. The instruments used in this study were the WHOQOL-BREF, Rosenberg Self-Esteem Scale (RSES), and Perceived Stress Scale (PSS). Multiple linear regression was conducted to identify significant relationships between the variables. Data were analyzed using univariate and bivariate analyses with Microsoft Excel and SPSS, presenting results as regression coefficients and 95% confidence intervals. Results The results of bivariate analysis in this study showed that health status, relevance of expectations, goals, and standards had a significant influence on quality of life ( p  < .05). In addition, our study found that self-esteem had a significant relationship with quality of life in first-semester student nurses ( p  = .010). Conclusion Based on the findings that first-semester nursing students experience moderate stress yet generally exhibit good self-esteem and quality of life, universities should prioritize assessments of students’ physical and psychological well-being during their adaptation period. It is recommended to implement counseling services, enhance support from guardian lecturers, and foster positive engagement with parents to address the expectations and goals influencing students’ quality of life. These strategies aim to improve overall well-being and academic success among new nursing students.